ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMILIHAN KONTRASEPSI SUNTIK SEBAGAI KB PASCA SALIN DI PUSKESMAS TERMINAL BANJARMASIN - Pratama Putri, Nanda; Lathifah, Nur; Noor Anisa, Fadhiyah (Midwifery And Complementary Care, 2024)
Background: In Indonesia in 2021 it was 57.4%. Based on provincial distribution, the highest prevalence rate of family planning use is south Kalimantan, which is 67.9%. Various factors influence postpartum mothers in choosing the right contraceptive according to their needs. Objective:. Analyze and identify what factors are related to the selection of Injectable Contraceptives as Postpartum Family Planning at the Banjarmasin Terminal Health Center. Methods: The method used in this study is the Cross Sectional method. By using a simple random sampling technique in sampling, the number of samples was obtained from 224 postpartum mothers. Data analysis using chi square test. Result: The results of the study that chose Injectable Birth Control were much more, namely 198 people (88.39%) compared to those who chose Non-Injectable Birth Control which was 26 people (11.61 %). The results of the chi square test on age were obtained that there were 25% cells with an expected value of < 5 so, the fisher exact test used with a p-value of 0.279. The results of the chi square test on education obtained a p-value with a value of 0.615. And the results of the chi square test against parity obtained a p-value with a value of 0.005. Conclusion: There is a relationship between parity and the selection of injectable contraceptives as postpartum birth control, while other factors such as age and education are not related to the selection of injectable contraceptives as postpartum birth control at the Banjarmasin Terminal Health Center.